AhR Activation by TCDD (2,3,7,8-Tetrachlorodibenzo-p-dioxin) Attenuates Pertussis Toxin-Induced Inflammatory Responses by Differential Regulation of Tregs and Th17 Cells Through Specific Targeting by microRNA - Al-Ghezi, Zinah Zamil; Singh, Narendra; Mehrpouya-Bahrami, Pegah; Busbee, Philip Brandon; Nagarkatti, Mitzi; Nagarkatti, Prakash S. (Frontiers in Microbiology, 2019)
The Aryl Hydrocarbon Receptor (AhR) is a ligand activated transcription factor implicated in the regulation of immune response. Pertussis Toxin (PTX) is a virulence factor found in Bordetella pertussis, a human respiratory pathogen that causes whooping cough. PTX promotes colonization and disease promotion by triggering heightened inflammatory response. The role of AhR in the regulation of PTX-mediated inflammation has not been previously studied. In the current study, we investigated if AhR activation by 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD), a well characterized ligand, can attenuate PTX-mediated systemic inflammation. To that end, C57BL/6 mice were injected twice i.p. with PTX and treated with TCDD or vehicle (VEH). PTX+VEH group had elevated levels of pro-inflammatory cytokines (IL-17A, IL-6, and IFNγ) in serum and increased proportions of CD4+ Th1 and Th17 cells in spleens. In contrast, PTX+TCDD group had significantly lower levels of these inflammatory cytokines and decreased proportions of Th1 and Th17 cells, but increased proportions of Th2 and FoxP3+Tregs when compared to PTX+VEH group. PTX+TCDD treated mice also had elevated levels of IL-10, and TFG-, potent anti-inflammatory cytokines. microRNAs (miRs) analysis of CD4+ T cells from the spleens of PTX+TCDD treated mice revealed significant alterations in their expression and several of these miRs targeted cytokines and signaling molecules involved in inflammation. Specifically, PTX+TCDD group had significantly enhanced expression of miR-3082-5p that targeted IL-17, and decreased expression of miR-1224-5p, which targeted FoxP3. Transfection studies with these miR mimics and inhibitors confirmed the specificity of the target genes. Together, the current study suggests that AhR activation by TCDD suppresses PTX-induced inflammation through miR regulation that triggers reciprocal polarization of Tregs and Th17 cells. These studies also suggest that AhR activation may serve as a treatment modality to suppress heightened inflammation induced during B. pertussis infection.